2011
DOI: 10.1149/1.3517430
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Thermal and Plasma-Assisted Atomic Layer Deposited Al[sub 2]O[sub 3] Thin Films

Abstract: A comparative electrical characterization study of aluminum oxide ͑Al 2 O 3 ͒ deposited by thermal and plasma-assisted atomic layer depositions ͑ALDs͒ in a single reactor is presented. Capacitance and leakage current measurements show that the Al 2 O 3 deposited by the plasma-assisted ALD shows excellent dielectric properties, such as better interfaces with silicon, lower oxide trap charges, higher tunnel barrier with aluminum electrode, and better dielectric permittivity ͑k = 8.8͒, than the thermal ALD Al 2 O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
45
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 32 publications
(41 reference statements)
10
45
0
Order By: Relevance
“…Correspondingly, the AP‐CVD diodes demonstrated superior asymmetry and nonlinearity at 1.4 V in Figure b,c when the conduction mechanism changed from Poole–Frenkel to Fowler–Nordheim tunneling at the turn on voltage. These results indicate that the insulator deposition method has an impact on the barrier height and MIM diode properties, consistent with previous reports …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Correspondingly, the AP‐CVD diodes demonstrated superior asymmetry and nonlinearity at 1.4 V in Figure b,c when the conduction mechanism changed from Poole–Frenkel to Fowler–Nordheim tunneling at the turn on voltage. These results indicate that the insulator deposition method has an impact on the barrier height and MIM diode properties, consistent with previous reports …”
Section: Resultssupporting
confidence: 93%
“…These barriers are illustrated schematically in the insets of Figure . The forward Al 2 O 3 –Al barrier heights of 2.20 and 2.80 eV observed in the AP‐CVD and PEALD diodes, respectively, are consistent with previously reported values of 2.25 and 2.47 ± 0.36 eV that were obtained theoretically and a value of 2.0 ± 0.2 eV obtained from photoemission studies . The lower barrier height observed for the AP‐CVD diodes in this work is consistent with a previous study that indicated that thermal ALD of Al 2 O 3 , which is similar to the AP‐CVD process used here, resulted in a barrier two times smaller than that obtained with PEALD .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…12 This means that in addition to the removal of -CH 3 group by oxygen radicals, which happens during the first 20 s of exposure, the extended exposure may have formed a denser and amorphous Al-O-Al network, which is in agreement with the O/Al ratio. 13 Currents for Al 2 O 3 and HfO 2 films were plotted versus applied voltage in Figs. 2(a) and 3(a).…”
Section: Results For Single Layer Of Al 2 O 3 or Hfomentioning
confidence: 99%
“…However characterizations based X-ray photoelectron spectroscopy (XPS) in dependence of the substrate temperature are not shown in that reviews. Furthermore to our knowledge there seems to be a lack in reports about dielectric parameters in dependence of the substrate temperature for PE-ALD as mostly comparisons are given at fixed temperatures [1,21] or only for T-ALD samples [22]. …”
Section: Introductionmentioning
confidence: 99%